Application of The Problem-Based Learning Model to Improve Mathematical Communication Ability of Senior High School Students - Silmi Ghaida; Al Jupri Al Jupri (MASI Mandiri Edukasi, 2026)
Mathematical communication is an important component of mathematics learning, yet many students in Indonesia still have difficulty expressing mathematical ideas clearly. This study aimed to examine whether students taught using the Problem-Based Learning (PBL) model achieve better mathematical communication skills and greater improvement than those taught using conventional instruction. This study used a quantitative approach with a quasi-experimental design, specifically a pretest–posttest non-equivalent control group design. The participants were 68 tenth-grade students from a senior high school in Bandung, divided into an experimental class and a control class using purposive sampling. Data were collected through written tests and observation sheets. The data were analyzed using the Mann–Whitney test and n-gain scores. The results showed that the experimental class had a higher posttest mean score than the control class, with a mean difference of 12.00 points. Statistical analysis indicated a significant difference between the two groups (p = 0.0315 < 0.05). In terms of improvement, the experimental class achieved a higher n-gain (0.53, medium category) compared to the control class (0.37, medium category), with a significant difference (p = 0.008 < 0.05). These findings indicate that the PBL model is effective in improving students’ mathematical communication skills and can serve as an alternative learning strategy in mathematics classrooms.